ANALISIS EKONOMI PEMANFAATAN JUS LIMBAH WORTEL (Daucus Carota L.) SEBAGAI FEED SUPPLEMENT TERNAK AYAM KAMPUNG - Hasrianti Silondae; Vicky Ventje Johan Panelewen; Jolanda Kitsia Juliana Kalangi (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the economic feasibility of utilizing carrot juice (Daucus carota L.) as feed supplement for native chicken. The study was conducted from April to July 2019 in the Pandu Experimental Garden in North Minahasa Regency. Economic analysis in the form of income analysis to determine the income derived from the livestock business by raising native chickens. If the value of TR> TC, the livestock business is profitable, if TR = TC, the livestock business is in a BEP condition, and if TR <TC, the livestock business loses. Business feasibility analysis includes price BEP, production BEP and R / C ratio. The results showed that the utilization of carrot juice (Daucus carota L.) as a feed supplement for native chicken livestock is economically feasible to be cultivated because it provides benefits based on economic analysis of R / C value> 1 and Break Event Point that is exceeded by product income and rupiah.*eprm*